2022
DOI: 10.1093/pm/pnac104
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin 8% Patch for Spinal Cord Injury Focal Neuropathic Pain, a Randomized Controlled Trial

Abstract: Background Neuropathic pain (NP) after spinal cord injury (SCI) exacerbates disability, decreases quality of life (QOL) and is often refractory to available therapies. Patients report willingness to trade potential recovery of strength, bowel, bladder, or sexual function for pain relief. One proposed mechanism causing NP is up-regulation of transient receptor potential vanilloid 1 (TRPV 1) proteins in uninjured C fibers and dorsal root ganglia causing neuronal excitability. Recent studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The capsaicin 8% patch provided effective pain relief with reduced application frequency and minimal systemic side effects compared to oral medications, like gabapentinoids or TCAs, in patients with painful diabetic peripheral neuropathy [ 99 ]. In a randomized controlled trial, the application of the capsaicin 8% patch for neuropathic pain in individuals with spinal cord injury was investigated, showing significant pain reduction, with improvements observed for pain outcome and mobility, but not in quality of life, measures [ 100 ]. In a systematic review of 5 studies including 95 patients, the efficacy and tolerability of 8% capsaicin patch was evaluated for its effectivess in mitigating the effects of chemotherapy-induced peripheral neuropathy, providing significant pain relief [ 101 ].…”
Section: Current Pharmacotherapies In Neuropathic Painmentioning
confidence: 99%
“…The capsaicin 8% patch provided effective pain relief with reduced application frequency and minimal systemic side effects compared to oral medications, like gabapentinoids or TCAs, in patients with painful diabetic peripheral neuropathy [ 99 ]. In a randomized controlled trial, the application of the capsaicin 8% patch for neuropathic pain in individuals with spinal cord injury was investigated, showing significant pain reduction, with improvements observed for pain outcome and mobility, but not in quality of life, measures [ 100 ]. In a systematic review of 5 studies including 95 patients, the efficacy and tolerability of 8% capsaicin patch was evaluated for its effectivess in mitigating the effects of chemotherapy-induced peripheral neuropathy, providing significant pain relief [ 101 ].…”
Section: Current Pharmacotherapies In Neuropathic Painmentioning
confidence: 99%
“…In an animal study, the activation of TRPV1 in the spinal cord by capsaicin produced excessive glutamate liberation causing acute pain [ 108 ]. A randomized control trial on patients affected by neuropathic pain reported a reduction of pain after treatment with capsaicin patches [ 109 ]. Mice treated with the endocannabinoid-like molecule palmitoylethanolamide (PEA) showed a decrease in pain derived from peripheral neuropathy, while using synthetic antagonists to block PPAR-α and CB1 receptors reversed this effect, demonstrating the mediation of these receptors in this process [ 110 ].…”
Section: Cannabinoids In Pancreatic Cancer Treatmentmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a debilitating condition which often leads to long-term or permanent mobility disability, chronic risk of various complications, and requires extensive medical resources. 1 , 2 An epidemiology study showed that the overall global incidence of SCI was 10.5 cases per 100,000 persons. 3 Although mobility is the most critical factor determining functional outcome, 4 additional sequelae such as neuropathic pain (NP), bladder and rectum dysfunctions also decrease quality of life considerably.…”
Section: Introductionmentioning
confidence: 99%